African Peacemaking and Governance Nairobi: Acton Publishers, 2007, 170pp (Hekima Review, 2008)
The book African Peacemaking and Governance is situated within the context of conflicts and political instability that has ravaged African countries. It seeks to adopt a methodology that aims at restoring social relationships. Our governments spend billions of dollars on weapons of war yet people die of hunger in refugee camps. The society is in disorder and armed conflicts are experienced on a daily basis.